Students' performance on engineering mathematics: Applying rasch measurement model - Aziz A.A.; Zaharim A.; Fuaad N.F.A.; Nopiah Z.M. (IEEE Computer Society, 2023)
This paper explores the students' performance on their basic engineering mathematics. It is essential for the students to meet the expectation of the engineering program in ensuring that the students be able to follow thru the whole program smoothly and achieved the expected learning outcome at the end of the program. Meaningful performance measurement is critical in identifying the performance of the students, and on the other hand identifies the weakness of the students. This study applies an entry test to new students for the engineering program in a local Malaysian higher learning institution. The test will enable students profiling according to their ability in mathematics, and would guide the lecturers to provide necessary remedial actions for the respective students. The Rasch measurement model is used to measure the students' ability against the engineering mathematics on the logit ability difficulty ruler. Rasch measurement model converts the test result from the test into ration type data and sorts the ability according to Rasch-Guttman matrix. This is the basis of Rasch measurement model in measuring the ability of the students by considering the difficulty of all the items involved in the test, and not just based on raw scores of the test. The correlation between all the students and all the items are displayed on a person-item distribution map for easy reading. 2013 IEEE.